Intracranial Atherosclerotic Plaque Characteristics and Burden Associated With Recurrent Acute Stroke: A 3D Quantitative Vessel Wall MRI Study - Sun, Beibei; Wang, Lingling; Li, Xiao; Zhang, Jin; Zhang, Jianjian; Liu, Xiaosheng; Wu, Hengqu; Mossa-Basha, Mahmud; Xu, Jianrong; Zhao, Bing; Zhao, Huilin; Zhou, Yan; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Intracranial atherosclerotic disease (ICAD) tends to affect multiple arterial segments, and previous studies rarely performed a comprehensive plaque analysis of the entire circle of Willis for the evaluation of recurrent stroke risk. We aimed to investigate the features of circle of Willis ICAD on 3D magnetic resonance vessel wall imaging (MR-VWI) and their relationships with recurrent acute stroke. Methods: Patients with either acute ischemic stroke (within 4 weeks after stroke) or chronic ischemic stroke (after 3 months of stroke) due to intracranial atherosclerotic plaque underwent 3D contrast-enhanced MR-VWI covering major cerebral arteries. Participants were divided into three groups: first-time acute stroke, recurrent acute stroke, and chronic stroke. Culprit plaque (defined as the only lesion or the most stenotic lesion when multiple plaques were present within the same vascular territory of the stroke) and non-culprit plaque characteristics, including total plaque number, plaque thickness, plaque area, plaque burden (calculated as plaque area divided by outer wall area), enhancement ratio (ER), eccentricity, and stenosis, were measured and compared across the three groups. Associations between plaque characteristics and recurrent acute stroke were investigated by multivariate analysis. Results: A total of 176 participants (aged 61 ± 10 years, 109 men) with 702 intracranial plaques were included in this study. There were 80 patients with first-time acute stroke, 42 patients with recurrent acute stroke, and 54 patients with chronic stroke. More intracranial plaques were found per patient in the recurrent acute stroke group than in the first-time acute stroke or chronic stroke group (5.19 ± 1.90 vs. 3.71 ± 1.96 and 3.46 ± 1.33, p < 0.001). Patients in the recurrent acute stroke group had greater culprit plaque burden (p < 0.001) and higher culprit ER (p < 0.001) than the other two groups. After adjustment of clinical demographic factors, in multivariate analysis, coronary artery disease (CAD) (odds ratio, OR = 4.61; p = 0.035), total plaque number (OR = 1.54; p = 0.003), culprit plaque ER (OR = 2.50; p = 0.036), and culprit plaque burden (OR per 10% increment = 2.44; p = 0.010) were all independently associated with recurrent acute stroke compared to the first-time acute stroke. Conclusion: Increased intracranial atherosclerotic plaque number, higher culprit plaque ER, greater culprit plaque burden, and CAD are independently associated with recurrent acute stroke.